Perancangan Aplikasi Mobile Segar Sehat Untuk Penjualan Produk Hortikultura Kebun Rumah Tangga Komplek Karyawan Pt X Dengan Menggunakan Metode Human Centered Design - Chindy Elsanna Revadi; Kamson Sirait (JURNAL AGRIBISNIS TERPADU, 2020)
Food security is an important aspect during the COVID-19 pandemic, especially in the horticulture sector. However, with the existence of Large-Scale Social Restrictions as a government policy to avoid the spread of COVID-19, the customer is expected to be able to maintain a distance from physical trading activities, so horticultural marketing should be able to focus on the household segment by utilizing digital marketing. Based on this, the application design "Fresh Sehat" is done by applying the Human-Centered-Design method. The results of usability testing on the "Fresh Sehat" application show that the average value of effectiveness, efficiency, and satisfaction is above 78% so that design improvements can be made by the problem findings by clarifying the details of the number of goods and the price to be ordered.